2022
DOI: 10.47197/retos.v47.94344
|View full text |Cite
|
Sign up to set email alerts
|

Assessing emotional, empathic and coping skills in Spanish undergraduates in Health Sciences and Social Sciences

Abstract: Background: Higher education is considered to be one of the phases in the life cycle that produces psychological distress and academic pressure. The aim of the study was to assess to assess the emotional, empathic and coping skills of undergraduate students of Health Sciences and Social Sciences undergraduates using an explorative approach in a cross sectional study. Methods: A sample of 693 first-to-fourth-year students enrolled in different degree courses. We used an “ad hoc” questionnaire, the Trait M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
1
10
0
4
Order By: Relevance
“…The fourth factor in this research was player personality, which refers to self-reliance, strong mentality, responsibility, and relentlessness, valuable personality traits in today's competitive football world. For example, self-reliance is the primary ingredient of self-confidence, which is essential for the athlete to move forward from loss and despair (Kolosov et al, 2019;Martínez Lorca et al, 2023). Dominado (2018) found that the loss of self-belief or selfresilience influences the athlete's perception of the emotional aspect.…”
Section: Discussionmentioning
confidence: 99%
“…The fourth factor in this research was player personality, which refers to self-reliance, strong mentality, responsibility, and relentlessness, valuable personality traits in today's competitive football world. For example, self-reliance is the primary ingredient of self-confidence, which is essential for the athlete to move forward from loss and despair (Kolosov et al, 2019;Martínez Lorca et al, 2023). Dominado (2018) found that the loss of self-belief or selfresilience influences the athlete's perception of the emotional aspect.…”
Section: Discussionmentioning
confidence: 99%
“…Автор розглядає емпатію не як єдиний уніполярний конструкт (тобто або когнітивний, або емоціональний), а підкреслює, що цей феномен краще уявляти як набір пов'язаних конструктів, які всі відносяться до відгуку на інших і в той же час вони всі ясно відрізняються один від одного. Виміри когнітивної складової є перспективними прийняття (PT) і фантазії (FS), тоді як афективний компонент складається з підшкал занепокоєння емпатією (EC) і особистого дистресу (PD) [5,19]. Підрахунок балів здійснюється по кожній шкалі шляхом складання балів відповідно до ключа методики.…”
Section: матеріали та методиunclassified
“…Вищі бали відображають тенденцію розвитку даного прояву. IRI має хороші психометричні властивості, він пройшов повноцінну процедуру апробації, має високу ступінь надійності, внутрішньої узгодженості, конструктної валідності, широко застосовується сучасними західними дослідниками емпатії [19,20]. Оскільки ця анкета створена для самостійного заповнення, шкала Девіса може бути швидко застосована та позитивно сприйнята [22].…”
Section: матеріали та методиunclassified
“…Estos factores afectan negativamente a la salud mental, siendo el estrés una respuesta fisiológica a tantos factores que interfieren en el bienestar, que requieren esfuerzos para adaptarse a las situaciones. El estrés excesivo y constante es una de las principales causas que desencadenan los trastornos mentales (RAIOL, 2020;ROEDER, 1999;MARTINEZ-LORCA, et al, 2023) .…”
Section: Introductionunclassified